Field‐aligned currents in Saturn's northern nightside magnetosphere: Evidence for interhemispheric current flow associated with planetary period oscillations. Issue 9 (26th September 2015) - Hunt, G. J.; Cowley, S. W. H.; Provan, G.; Bunce, E. J.; Alexeev, I. I.; Belenkaya, E. S.; Kalegaev, V. V.; Dougherty, M. K.; Coates, A. J.
Abstract We investigate the magnetic perturbations associated with field‐aligned currents observed on 34 Cassini passes over the premidnight northern auroral region during 2008. These are found to be significantly modulated not only by the northern planetary‐period oscillation (PPO) system, similar to the southern currents by the southern PPO system found previously, but also by the southern PPO system as well, thus providing the first clear evidence of PPO‐related interhemispheric current flow. The principal field‐aligned currents of the two PPO systems are found to be co‐located in northern ionospheric colatitude, together with the currents of the PPO‐independent (subcorotation) system, located between the vicinity of the open‐closed field boundary and field lines mapping to ~9 Saturn radius (Rs) in the equatorial plane. All three systems are of comparable magnitude, ~3 MA in each PPO half‐cycle. Smaller PPO‐related field‐aligned currents of opposite polarity also flow in the interior region, mapping between ~6 and ~9 Rs in the equatorial plane, carrying a current of ~ ±2 MA per half‐cycle, which significantly reduce the oscillation amplitudes in the interior region. Within this interior region the amplitudes of the northern and southern oscillations are found to fall continuously with distance along the field lines from the corresponding hemisphere, thus showing the presence of cross‐field currents, with the southern oscillations being dominant in the south, and modestly lower in amplitude than the northern oscillations in the north. As in previous studies, no oscillations related to the opposite hemisphere are found on open field lines in either hemisphere.